Transnasal endoscopic repair of pediatric meningoencephalocele - Keshri, Amit Kumar (J Pediatr Neurosci, 2016)
INTRODUCTION: Encephaloceles in relation to the nose are rare lesions affecting the skull base. In the pediatric population, majority are congenital lesions manifesting as nasal masses requiring surgical intervention. MATERIALS AND METHODS: A retrospective study of 6 consecutive patients below 12 years of age with intranasal meningoencephalocele treated by endonasal endoscopic approach at our tertiary centre was done. The follow up period ranged from 6 months to 2 years. A detailed clinical and radiological evaluation of these cases was done. Endonasal endoscopic repair (gasket seal/fat plug) was carried out in all cases. RESULTS: Out of 6 patients, 4 patients had post-traumatic and rest 2 cases had congenital meningo-encephaloceles. All patients were asymptomatic in post-operative follow up period. One patient had minor complication of nasal alar collapse due to intra-operative adherence of encephalocele to cartilaginous framework. CONCLUSION: Transnasal endoscopic repair of anterior skull base meningoencephalocele is a minimally invasive single stage surgery, and has advantage in terms of lesser hospital stay, cost of treatment, and better cosmesis. The repair technique should be tailored to the size of defect to provide a water-tight seal for better outcome.